Understanding College Intention in Rural Education Context - Willson Gustiawan; Muhammad Ilham Afriansyah; Rahmat Eka Putra (Department of Management, Universitas PGRI Yogyakarta., 2026)
Purpose: This study investigates the extent to which learning motivation and perceived parental financial support influence students’ intention to pursue higher education, focusing on 11th-grade students in a rural Indonesian high school. It addresses a research gap concerning educational aspirations among underserved youth in developing regions. Methodology: A quantitative explanatory design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Data were collected from 127 purposively selected students at SMAN 1 X Koto Singkarak. Constructs for learning motivation, perceived parental financial support, and college intention were measured using validated items on a 5-point Likert scale. The analysis assessed the measurement model (validity and reliability) and structural model (path coefficients). Findings: Both learning motivation (β = 0.344; p < 0.001) and perceived parental financial support (β = 0.219; p < 0.01) positively and significantly influence college intention. The model explains 20.2% of the variance in students’ educational aspiration (R² = 0.202). Learning motivation was the stronger predictor, highlighting the critical role of internal psychological drivers despite economic limitations. Originality: This research offers new insights into how psychological and economic factors jointly shape college aspirations in rural settings. By integrating Self-Determination Theory within a socio-economic framework using PLS-SEM, the study contributes both theoretically and methodologically Research limitations: Findings are limited to a single rural school, reducing generalizability. The cross-sectional design limits causal inference, and self-reported data may involve bias. Future studies should use broader samples, longitudinal designs, and explore mediating variables such as peer or institutional influence. Practical implications: The results suggest schools and policymakers should foster student motivation through mentoring and goal-setting, while also enhancing financial access via scholarships and outreach to promote higher education participation in rural areas.